A Trefoil Knotted Polymer Produced through Ring Expansion1. Issue 17 (27th February 2015) - Cao, Peng‐Fei; Mangadlao, Joey; Advincula, Rigoberto
Abstract A synthetic strategy is reported for the production of a trefoil knotted polymer from a copper(I)‐templated helical knot precursor through ring expansion. The expected changes in the properties of the knotted polymer compared to a linear analogue, for example, reduced hydrodynamic radius and lower intrinsic viscosity, together with an atomic force microscopy (AFM) image of individual molecular knots, confirmed the formation of the resulting trefoil knotted polymer. The strategies employed here could be utilized to enrich the variety of available polymers with new architectures.